CASE REPORT: DERMATITIS IN A MIX DOG WITH TOPICAL CANDLENUT OIL THERAPY AND FINDING OF ANCYLOSTOMA SPP. INFECTION - Ni Luh Putu Suarniti; Putu Ayu Sisyawati Putriningsih; I Nyoman Suartha (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Dermatitis is one of the most common skin problems in dogs and can be accompanied by various clinical manifestations such as pruritus, erythema, papules, scaling, hyperpigmentation, and alopecia. This condition is multifactorial and can be caused by both infectious and non-infectious factors. Ancylostoma spp. infestation in dogs is known to cause gastrointestinal disorders, particularly anemia due to chronic blood loss. However, this infestation can also be associated with dermatological manifestations such as dermatitis and alopecia, which are related to percutaneous larval migration and the systemic impact of the resulting anemia. This case report describes the diagnosis and treatment of dermatitis and Ancylostoma spp. infection in a 1-year-old mixed-breed female dog with symptoms of generalized alopecia, pruritus, erythema, hyperpigmentation, scaling, papules, and scooting, as well as a thin body condition. Diagnostic methods included clinical examination and skin, fecal, and complete blood count examinations. The results revealed the presence of Ancylostoma spp. eggs, skin examination revealed no detectable ectoparasites or dermatological pathogens, and the blood test results showed lymphocytosis, granulocytopenia, and mild thrombocytopenia. Treatment included a combination of pyrantel pamoate as an anthelmintic, chlorpheniramine maleate as an antihistamine, vitamin B-complex supplements, and topical candlenut oil to support skin regeneration and promote hair growth. Clinical evaluation over 14 days showed significant improvement, with the disappearance of pruritus, new hair growth, and a negative stool test for worm eggs. This combination therapy approach has proven effective and can be an alternative natural treatment that supports skin recovery in cases of dermatitis and Ancylostoma spp. infection.